Interfacial reaction mechanism during laser brazing of Zn-Mg-Al-coated steel to AA 6061 aluminum alloy - Javadinejad, Hamid Reza; Lee, Mokyoung; Shim, Cheol Hwee; Chang, Hye Jung; Kim, Jeoung Han (Elsevier BV, 2022)
Ternary Zinc-Aluminum-Magnesium coatings are attracting significant attention in the automotive and steel industries because of their superior corrosion resistance and stability over traditional Zn-based coatings. However, the literature on this new type of coating is limited and focuses mostly on corrosion resistance. The purpose of the present study was to extend our understanding of these coatings by gaining insight into the weldability with dissimilar alloys. Owing to their different physical and mechanical properties, it is known to be difficult to join dissimilar materials. In this study, Zn-Al-Mg ternary coated steel was brazed to AA 6061 aluminum alloy by laser brazing using an Al-Zn filler material. The results revealed that various kinds of intermetallic compounds were formed at the interface of the materials, with different compositions in the AA 6061 and steel regions. This resulted in distinct variations in the elemental distribution, morphology, and mechanical properties of the Al/ brazement and steel/brazement interfaces. Furthermore, it was observed that the tensile and fracture properties of the brazement are dependent on both the materials and brazing conditions. The main intermetallic component was Fe2Al5, which was observed at both interfaces of the brazement.